2017
DOI: 10.1186/s40066-016-0082-4
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable diversification in cocoa-based farming systems Ghana

Abstract: Background: As part of dynamic livelihood coping strategies, some farmers in Ghana's cocoa belt have diversified away from traditional cocoa production to other high-value crops including vegetables, to the extent of diversifying within vegetables. This study assessed the extent of diversification of vegetables among farmers in Ghana's cocoa belt and determined the factors that explain the variability in the diversification indices. A small-sample-size formula (http://www.surveysystem.com/sscalc.htm) that was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Such farm households earn additional incomes directly from the sale of food products including plantain, yams, fruits, honey, vegetables etc., and indirectly from monies saved that would have been otherwise used to buy food [41]. Furthermore, through agroforestry practices that increase carbon stocks on-farm and hence reduce GHG emissions, CSA/Agroecology provides a potential opportunity for additional household incomes from carbon credits through the result-based national REDD+ programme [42].…”
Section: Contributions Of Csa/agroecology To Productivity and Incomementioning
confidence: 99%
See 1 more Smart Citation
“…Such farm households earn additional incomes directly from the sale of food products including plantain, yams, fruits, honey, vegetables etc., and indirectly from monies saved that would have been otherwise used to buy food [41]. Furthermore, through agroforestry practices that increase carbon stocks on-farm and hence reduce GHG emissions, CSA/Agroecology provides a potential opportunity for additional household incomes from carbon credits through the result-based national REDD+ programme [42].…”
Section: Contributions Of Csa/agroecology To Productivity and Incomementioning
confidence: 99%
“…However, this potential raises questions on equity concerning how farmers would be fairly rewarded from carbon credits and other related benefits for achieving mitigation benefits. This is because there is not yet clarity on key issues around the development of a fair and transparent benefit sharing scheme and carbon rights definition, land and tree tenure and gender mainstreaming mechanisms are still outstanding, which have dominated the REDD+ implementation discourse [41].…”
Section: Contributions Of Csa/agroecology To Productivity and Incomementioning
confidence: 99%
“…Integrating vegetables into maize-based farming systems as a means to augment household income is appropriate due to their high farm gate values per unit land and economic access to diverse food groups [7]. More diverse production systems may contribute to more diverse household diets for farming communities [12]. Reducing the prevalence of micronutrient deficiencies will not be sustainable if food consumption is not diversified [31,61].…”
mentioning
confidence: 99%
“…Some studies have shown that an increase in household dietary diversity is associated with higher socioeconomic status and household food security measured in terms of household food energy availability ( [1,12,15,23,27,39,43,45,58,20]). Household dietary diversity is also associated with monthly per capita calorie availability from non-staples for all households [23] and household expenditure which is a proxy for household wealth and well-being [58].…”
mentioning
confidence: 99%
See 1 more Smart Citation